Socio-demographic variables influence on media literacy towards soft drink advertisement among adolescents in Klang Valley, Malaysia - M. S., Nur Nadirah; Othman, Mohhidin; Ghazali, Hazrina; Abu Bakar, Ainul Zakiah (American-Eurasian Network for Scientific Information (AENSI) Publications, 2015)
Background: Media literacy was found to be a preventive method from being misled by soft drink advertising. Objectives: The purpose of this paper is to present research findings on media literacy towards soft drink advertisement among adolescent in Malaysia. This paper also examines the influence of adolescents’ socio-demographic variable towards their media literacy on soft drink advertisement. Results: Results revealed that 45.1% of respondents possess good level of media literacy. Additionally, gender, age, ethnicity and grade of respondents were examined individually to determine the influences on respondents’ media literacy score. However, the findings of this research show that respondents’ media literacy score on soft drink advertisement differed across grades variable only (F = 6.511, p = 0 .000). The total media literacy score on soft drink advertisement was significantly positively correlated with grades (r = 0.328, p<.05). Conclusion: It indicates that grades of adolescent could affect their media literacy. The importance of this study is to help the authorities, soft drink marketers and producers to better understand media literacy on soft drink advertisement among adolescent in Malaysia.